Al-Qiyam al-Thaqāfīyah wa Ṭābi‘ al-Sha‘b li Jayl al-Muslimīn al-Shubbān al-Indūnīsīyīn - Aan Hasanah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2015)
Cases of negative social behavior among students happen not only in public schools but also in madrasah. Actually, madrasah should be the right place for implanting character values because they teach religious education over more hours, and does so more comprehensively than public schools. However, the fact is the process has not run effectively due to how religious education is taught merely as a knowledge. Besides, madrasah conntinue to face internal and external problems. To deal with these problems, a model of implanting cultural values and national characters using a comprehensive approach based on Lickona’s theory is one of the solutions to developing positive characters values within madrasah. The theory recommends the adoption of an comprehensive implementation strategy inside and outside of the classroom, with it done in an integrated manner. This kind of implementation requires all parties—madrasah, parents, government and society—to be involved consistently in developing character values.DOI: 10.15408/sdi.v22i3.2356